2022
DOI: 10.3390/su14127035
|View full text |Cite
|
Sign up to set email alerts
|

U.S. Consumer Attitudes toward Antibiotic Use in Livestock Production

Abstract: Antimicrobial resistance, which decreases the efficacy of antibiotics and other antimicrobials, has led to concerns about the use of antibiotics in livestock production. Consumers play an important role in influencing producers’ decisions about the use of antimicrobials through their choices in the marketplace, which are driven by attitudes toward these practices. This study examines consumers’ levels of concern about (and acceptance of) the use of antibiotics in livestock production for four objectives: to tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…Our sample was predominantly female, younger, and more highly educated than the adult US population. Women tend to be more likely to be primary shoppers, so it is not surprising that the sample had a higher percentage of women than men and, in fact, this was similar to the percentage of women in previous studies that targeted primary shoppers [33,34,72,73]. Individuals with higher education levels tend to have better outcomes [63,74], while older individuals pay greater attention to certain aspects of food choices [33].…”
Section: Discussionsupporting
confidence: 68%
“…Our sample was predominantly female, younger, and more highly educated than the adult US population. Women tend to be more likely to be primary shoppers, so it is not surprising that the sample had a higher percentage of women than men and, in fact, this was similar to the percentage of women in previous studies that targeted primary shoppers [33,34,72,73]. Individuals with higher education levels tend to have better outcomes [63,74], while older individuals pay greater attention to certain aspects of food choices [33].…”
Section: Discussionsupporting
confidence: 68%
“…But acceptance can vary with the use of the antibiotic. Meerza et al [30] found that only 14% of US consumers found antibiotic use as a growth promoter acceptable, but over 50% found the use of antibiotics to treat and control infections acceptable. Some consumers expect that no use of antibiotics means better animal welfare, when the opposite may well be true [28,30].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Meerza et al [30] found that only 14% of US consumers found antibiotic use as a growth promoter acceptable, but over 50% found the use of antibiotics to treat and control infections acceptable. Some consumers expect that no use of antibiotics means better animal welfare, when the opposite may well be true [28,30]. Meerza et al [30], for example, found that US respondents who believed antibiotic use reduces animal welfare were more likely to be concerned about the use of antibiotics to treat, prevent and control disease than respondents who viewed antibiotics as contributing to better animal welfare.…”
Section: Literature Reviewmentioning
confidence: 99%
“…On the other hand, some consumers considered the preventive use of antibiotics as a normative and standard practice in farming [ 62 ]. Research in the US revealed that only about one third of consumers were very concerned about the preventive use of antibiotics in food animals and even less of them considered the preventive use as unacceptable [ 61 ]. These findings suggested that consumers have little knowledge about the preventive use of antibiotics in food animals and limited understanding of the health risks associated with it.…”
Section: Introductionmentioning
confidence: 99%